Reliability Evaluation of Electric Power Generation PLTS System on Public Street Lighting Tarakan City - Apriliandy, M. Tesar; Budiman, Achmad (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
Public street lighting (PJU) is a lighting lamp that is public (for the common good) and is usually installed on the road. Solar Public Street Lighting (PJU-TS) is a public street lighting where the electrical power for the lights is supplied by a Stand Alone system that uses solar energy. In this study, measurements of sunlight, lamplight intensity, and lamppost height were carried out on 24 PJU-TS units spread across 4 sub-districts in Tarakan city. Furthermore, simulating PJU-TS using Matlab Simulink to determine the level of reliability based on the use or usage of batteries in PJU-TS. Based on the regulation of the Minister of Transportation of the Republic of Indonesia Number PM 27/2018 concerning Street Lighting Equipment that the lighting level of PJU-TS lamps is 3-6 lux and based on recommendations from the Reliability Standard Power Plant that the reliability value is at least 80%. The results of this research simulation that PJU-TS that meets the standards of the Minister of Transportation of the Republic of Indonesia Number PM 27/2018 amounted to 3 units of 3-6 lux, 40 W lamps, lamp working hours 11 hours 14 minutes, 300 WP solar modules, solar charge controller current 15.72 A, 40 Ah batteries, battery working hours 13.72-18.68 hours, percentage of Ah battery usage 46.42% - 95%. In addition to meeting the standards of the Minister of Transportation of the Republic of Indonesia Number PM 27/2018, the results of this simulation also meet the Reliability Standard Power Plant recommendations with reliability exceeding 80%, namely 81.27% - 100%. Meanwhile, 21 units of PJU-TS do not meet the standards of the Minister of Transportation of the Republic of Indonesia Number PM 27/2018 concerning Street Lighting Equipment and Reliability Standard Power Plant recommendations.